Hot subdwarf binaries - Masses and nature of their heavy compact companions - Geier, Stephan; Heber, Ulrich; Edelmann, Heinz; Kupfer, Thomas; Napiwotzki, Ralf; Podsiadlowski, Philipp (2009)
Neutron stars and stellar-mass black holes are the remnants of massive stars, which ended their lives in supernova explosions. These exotic objects can only be studied in relatively rare cases. If they axe interacting with close companions they become bright X-ray sources. If they are neutron stars, they may be detected as pulsars. Only a few hundred such systems are presently known in the Galaxy. However, there should be many more binaries with basically invisible compact objects in non-interacting binaries.Here we report the discovery of unseen compact companions to hot subdwarfs in close binary systems. Hot subdwarfs are evolved helium-core-burning stars that have lost most of their hydrogen envelopes, often due to binary interactions. Using high-resolution spectra and assuming tidal synchronisation of the subdwarfs, we were able to constrain the companion masses of 31 binaries. While most hot subdwarf binaries have white-dwarf or late-type main sequence companions, as predicted by binaxy evolution models, at least 5% of the observed subdwarfs must have very massive companions: unusually heavy white dwarfs, neutron stars and, in some cases, even black holes. We present evolutionary models which show that such binaries can indeed form if the system has evolved through two common-envelope phases. This new connection between hot subdwarfs, which are numerous in the Galaxy, and massive compact objects may lead to a tremendous increase in the number of known neutron stars and black holes and shed some light on this dark population and its evolutionary link to the X-ray binaxy population.